2022
DOI: 10.1097/hs9.0000000000000794
|View full text |Cite
|
Sign up to set email alerts
|

Immune Biomarkers in the Peripheral Blood and Tumor Microenvironment of Classical Hodgkin Lymphoma Patients in Relation to Tumor Burden and Response to Treatment

Abstract: In classical Hodgkin lymphoma (cHL), the malignant cells represent only a small fraction of the tumor. Yet, they orchestrate a lymphocyte-dominated tumor microenvironment (TME) that supports their survival and growth. The systemic effects of this local immunomodulation are not fully elucidated. Here, we aimed at characterizing circulating lymphocytes and plasma proteins in relation to clinical parameters and treatment effect. Peripheral blood (PB) samples were obtained from 48 consecutive patients at diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
0
8
0
2
Order By: Relevance
“…In patients compared to controls, larger percentages of CD4 + and CD8 + T cells expressed the inhibitory molecules PD-1 and CTLA-4, indicating that their T cells are exhausted. The proportions of CTLA-4 + CD4 + and CD8 + T cells as well as the fractions of PD-1 + CD8 + T cells reduced after standard-of-care first-line therapy [23] . Accordingly, it appears that anti-PD-1 therapy combined with chemotherapeutic agents [34] and anti-PD-1 monotherapy [22] in HL patients reverses T-cell exhaustion.…”
Section: Pd-l1 + and Cytotoxic T Lymphocyte Antigen (Ctla)-4 + T Cellsmentioning
confidence: 96%
See 3 more Smart Citations
“…In patients compared to controls, larger percentages of CD4 + and CD8 + T cells expressed the inhibitory molecules PD-1 and CTLA-4, indicating that their T cells are exhausted. The proportions of CTLA-4 + CD4 + and CD8 + T cells as well as the fractions of PD-1 + CD8 + T cells reduced after standard-of-care first-line therapy [23] . Accordingly, it appears that anti-PD-1 therapy combined with chemotherapeutic agents [34] and anti-PD-1 monotherapy [22] in HL patients reverses T-cell exhaustion.…”
Section: Pd-l1 + and Cytotoxic T Lymphocyte Antigen (Ctla)-4 + T Cellsmentioning
confidence: 96%
“…The latest study found that CHL patients displayed higher levels of proliferative T cells, higher concentrations of the circulating T cell markers, CTLA-4 and PD-1, and lower concentrations of naive T-cell frequencies in comparison to controls [23] .…”
Section: Pd-l1 + and Cytotoxic T Lymphocyte Antigen (Ctla)-4 + T Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, most of the immunomodulatory strategies for anti-cancer treatments focus on enhancing T-cell response ( Shimu et al, 2023 ). Moreover, abnormal expression of MHC I on tumor cells and upregulation of PD-L1 are associated with poor prognosis in Hodgkin lymphoma patients, thus suggesting that immune response is independent of T-cells, inhibited by PD-1, and rescued by PD-L1 blockade ( Mulder et al, 2022 ). Natural killer (NK) cells have cytolytic activity and are involved in the immune monitoring of tumor cells and virus-infected cells ( Peng et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%